2020
DOI: 10.4081/aiua.2020.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Urological emergency activities during COVID-19 pandemic: Our experience

Abstract: Background: The Coronavirus Disease (COVID-19) is causing a significant health emergency which is overturning dramatically routine activities in hospitals. The outbreak is generating the need to provide assistance to infected patients and in parallel to treat all nondeferrable oncological and urgent benign diseases. A panel of Italian urologists agreed on possible strategies for the reorganization of urological routine practices and on a set of recommendations that should facilitate a further planning of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…A recent systematic review demonstrated that access to the operating theatre is almost exclusively restricted to emergencies and oncological procedures [32]. Further research into COVID-19 effects on urologic emergencies was conducted, with one study demonstrating that urgent care visits from patients directly to the emergency department decreased (from 219 to 107) while those urgent care visits who were referred by their general practitioners remained unchanged (74 to 72) when comparing the same periods (from March 9th to April 14th) in 2020 (during the time of COVID-19 pandemic) and 2019 (before the pandemic) [33]. The same study highlighted that the rate of visits for each of the emergencies including the acute scrotum, acute urinary retention, hematuria, cystitis, prostatitis, sepsis, and genito-urinary trauma from the emergency department and general practitioners remained unchanged when comparing the two time periods [33].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A recent systematic review demonstrated that access to the operating theatre is almost exclusively restricted to emergencies and oncological procedures [32]. Further research into COVID-19 effects on urologic emergencies was conducted, with one study demonstrating that urgent care visits from patients directly to the emergency department decreased (from 219 to 107) while those urgent care visits who were referred by their general practitioners remained unchanged (74 to 72) when comparing the same periods (from March 9th to April 14th) in 2020 (during the time of COVID-19 pandemic) and 2019 (before the pandemic) [33]. The same study highlighted that the rate of visits for each of the emergencies including the acute scrotum, acute urinary retention, hematuria, cystitis, prostatitis, sepsis, and genito-urinary trauma from the emergency department and general practitioners remained unchanged when comparing the two time periods [33].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Although there are similar studies in the literature, these studies generally covered a period of several months during the 1 st months of the pandemic. [2,3] Our study, on the other hand, is the first study that discussed a slightly longer period of 8 months and compared it with the previous year.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, along with the effect of restrictions such as the curfew announced during the 1 st months of the pandemic, there was a significant decrease in non-COVID patient admissions to hospitals, which is considered to be due to the fact that patients could not apply to hospitals by delaying their complaints for the fear of COVID-19. [2][3][4] We consider that emergency surgical procedures increased during the pandemic period as a result of this delay.…”
mentioning
confidence: 99%
“…Our study showed that there was a decrease of 31.05% in admissions to the emergency department during the 8-month pandemic period compared to the previous year in a similar period. In the studies covering the early stages of the pandemic, it was reported that there was a decrease in admissions to the emergency department (14,15). In a study covering the first 4-week early pandemic period in America, this decrease was found to be 42%, and another study found a decrease of 31%-45% although there was a difference by regions in America (16,17).…”
Section: Discussionmentioning
confidence: 99%